Design for optimizing copper extraction from aqueous solution using LIX984N extractant - Nyamdelger, Shirchinnamjil; Khulan, Byambasuren; Narangarav, Tumen-Ulzii; Ulziibadrakh, Erdenebat; Sarantsetseg, Purevsuren; Azzaya, Tumendelger; Alen, Silam; Enkhtuul, Surenjav; Burmaa, Gunchin (Bulletin of the Institute of Chemistry and Chemical Technology, 2023)
Copper sulfide concentrate, containing chalcopyrite (CuFeS2), chalcocite (Cu2S), and covellite (CuS) was subjected to low temperature (4000C) oxidation roasting, resulting in water-soluble copper sulfate and insoluble iron oxides. Both chemical and ICP-OES analysis revealed that samples after oxidation roasting contain Cu 28.34%, S 14.37%, Fe 11.28%, Zn 0.35%, Sb 0.58%, As 0.20%, SiO2 5.94%, and Ag 0.65%. The copper dissolution rate of the roasted sample in water was estimated to be 98.48%. This study applied mathematic planning through central composite design (CCD) by “Design Expert 13”, a software to help optimize copper extraction from an aqueous solution using LIX984N, an organic extractant. The key extraction parameters, i.e. pH, extractant concentration, and duration extraction were screened to minimize the number of experiments. The results we discuss, indicate that the pH of solution, and concentration of the extractant are the most influential factors in copper extraction. The interplay between pH, extractant concentration, and extraction time was visualized through 3D-factorial design. Statistical analysis, such as ANOVA (Analysis of variance) parameters P value, F value, as well as the regression coefficient (R2) revealed their positive interdependence. The optimal conditions for extraction were determined as follows: LIX984N extractant concentration of 2.2%, copper solution pH of 2, and an extraction time of 2.5 minutes, which resulted in a maximum copper extraction rate of up to 99.5%. Усан уусмал дахь зэс (II)-ийн LIX984N хандлагчаар хандлагдах нөхцөлийг оновчлох загварчлал Хураангуй: Халькопирит, халькозин, ковеллин бүхий зэсийн сульфидын баяжмалыг нам температур (400°C)-т, хүчилтөрөгчийн орчинд исэлдүүлэн шатаахад усанд уусдаг зэсийн сульфат болон уусдаггүй төмөр (II, III)-ийн ислүүд үүссэн. Исэлдүүлэн шатаасан дээжид химийн болон индукцийн холбоот плазмын спектроcкоп (ICP-OES)-ийн аргаар Cu 28.34%, S 14.37%, Fe 11.28%, Zn 0.35%, Sb 0.58%, As 0.20%, SiO2 5.94%, Ag 0.65% тодорхойлогдсон. Тус дээжийг усанд уусгахад зэсийн сульфатын уусалтын зэрэг 98.48% байсан. Усан уусмал дахь зэс (II)-ийн LIX984N органик хандлагчаар хандлагдах нөхцөлийг загварчлалаар оновчлох судалгаа хийсэн. Хандлалтын нөхцөлийг оновчлох судалгаанд “Design Expert 13” программын математик төлөвлөлтийн төвийн композит загвар (CCD - Central Composite Design)-ыг ашиглав. ССD аргаар загварчлахын тулд хандлалтын параметрүүд (рН, хандлагчийн концентрац, хугацаа)-ад скрининг хийж, туршилтын хамгийн бага тоо (Min Run Res V)-г төлөвлөж, зэс (II)-ийн хандлалтад уусмалын рН, хандлагчийн концентрац хамгийн их нөлөөтэйг тодорхойлов. Тусгалын гадаргуугийн 3 хэмжээст графикаар хүчин зүйлүүд (рН, хандлагчийн концентрац, хугацаа)-ийн хамаарлыг харуулж, эдгээр хүчин зүйлүүд харилцан эерэг хамааралтайг хувьсагчдын харилцан үйлчлэлийн нөлөөллийн регрессийн коэффициент (R2), P-утга, F-утга зэрэг статистик шинжилгээ (ANOVA - Analysis of Variance буюу хувьсагчийн анализ)-ний дүнг үндэслэн хандлах туршилтын оновчтой нөхцөл: LIX984N хандлагчийн концентрац 2.2%, уусмалын pH=2, хандлалтын хугацаа 2.5 минут гэж оновчлов. Энэ нөхцөлд зэсийн хандлалтын зэрэг хамгийн их буюу 99.5% байв. Түлхүүр үг: LIX984N, зэсийн сульфид, төвийн композит төлөвлөлтийн загварчлал (CCD)